واقع مساهمة التعليم المفتوح في خدمة المجتمع دراسة تطبيقية في جامعة تشرين خلال الفترة 2002-2015 - العلي, إبراهيم; نادر, سناء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى دراسة واقع مساهمة التعليم المفتوح بجامعة تشرين في خدمة المجتمع, وذلك من خلال دراسة واقع وتطور أعداد الطلاب المستجدين والمسجلين والمتخرجين, وواقع وتطور الإيرادات والنفقات, وتحديد الفائض لخدمة المجتمع. اعتمد البحث على المنهجين التاريخي والوصفي, وتمّ اعتماد سلسلة زمنية تمتد من العام 2002 ولغاية العام 2015, وكان من أهم النتائج: إنّ كل من إيرادات ونفقات التعليم المفتوح ومساهمتهما في خدمة المجتمع تأخذ خطاً متزايداً مع الزمن خلال الفترة 2002-2015, حيث بلغ المجموع المتراكم لمساهمة التعليم المفتوح في خدمة المجتمع خلال الفترة 2002-2015 ما مقداره (278.955.940) ليرة سورية. ومن الملاحظ أنّ الفائض المتوقع لخدمة المجتمع من إيرادات التعليم المفتوح خلال الفترة 2016-2002 يقدر بـ (2.941.245.669) ليرة سورية.The research aims to study the reality and the evolution of inputs and outputs of Open Learning at Tishreen University, and assess their contribution to community service, and through the study of the reality and the evolution of the number of new students enrolled and graduating, and the reality and the evolution of revenues and expenditures, and determine the surplus to serve the community. Adopted research on historical and descriptive approaches, was the adoption of a time series that runs from 2002 until 2015, and it was the most important results: all of the income and expenditures of open learning and contribution to the community service takes a growing line with the times during the period from 2002 to 2015, where the total accumulated amount the contribution of open education in community service during the period 2002-2015 amounted to (278.955.940) LS. It is noted that the surplus is expected to serve the community of open education revenues during the period 2016-2002 is estimated at (2.941.245.669) LS.